Improving Students' Science Process Skills and Critical Thinking Skills in Physics Learning through FERA Learning Model with SAVIR Approach. (February 2020) - Diani, Rahma; Latifah, Sri; Jamaluddin, Wan; Pramesti, Ardya; Susilowati, Nur Endah; Diansah, Irani
Abstract: This study aimed to determine the effectiveness of FERA learning model (Focus, Explore, Reflect and Apply) with SAVIR approach in improving students' science process skills and critical thinking skills in physics learning. The method used in this research was Quasi-Experiment with non-equivalent control group design. The subject of this research was students in one of the senior high schools in Lampung District. MANOVA test (Multivariate of Variance) in SPSS 20 was used as a hypothesis test. The analysis result showed that there were differences in science process skills and critical thinking skills between the experimental class and the control class. The effectiveness of FERA learning model with SAVIR approach in improving students' science process skills and critical thinking skills in physics learning was tested by Effect Size test. The results showed that FERA learning model with SAVIR approach was more effective in improving students' science process skills and critical thinking skills than using discovery learning model.